Socialization and Training of Aromatic Candle Processing from Used Cooking Oil for Urban Residents - Lisanty, Nina; Wiwiek Andajani; Kresna Widigdo Margo Utomo; Nixie Azalia Whintisna; Rizki Jefri Ramadhan (Universitas Pendidikan Ganesha, 2023)
This article highlights a community initiative aimed at promoting sustainable household liquid waste management in Kediri City, Indonesia. The problem identified was the insufficient attention given to liquid waste, particularly used cooking oil, which often leads to environmental pollution and infrastructure damage. The objective of the activity was to raise awareness among residents about the proper disposal and recycling of used cooking oil. The proposed approach involved conducting workshops, training sessions, and awareness campaigns to educate community members about the environmental impacts of improper disposal and the benefits of recycling used cooking oil into aromatic candles. Major findings revealed that through collaborative efforts with local officials and community organizations, the initiative successfully engaged community members and fostered a sense of responsibility towards waste management. The training programs empowered participants with practical skills to convert used cooking oil into aromatic candles, promoting the repurposing of waste while creating a pleasant atmosphere. The conclusion emphasizes the importance of community participation and public awareness in ensuring sustainable liquid waste management. The initiative showcased the feasibility of recycling used cooking oil and highlighted the potential for broader adoption of similar practices in other regions. Overall, the activity underscored the significance of individual actions in collectively addressing environmental challenges and encouraged the adoption of responsible waste management practices at the household level.